2001
DOI: 10.1016/s0014-5793(01)02409-7
|View full text |Cite
|
Sign up to set email alerts
|

An integrated approach in the discovery and characterization of a novel nuclear protein over‐expressed in liver and pancreatic tumors

Abstract: An integrated approach in protein discovery through the use of multidisciplinary tools was reported. A novel protein, Hcc-1, was identified by analysis of the hepatocellular carcinoma (HCC)-M cell proteome. The assembled EST sequence of the 210 amino acid novel protein was subsequently confirmed by rapid amplification of cDNA ends (RACE). A total of 687 bp at the 5P P untranslated region of Hcc-1 was identified. Promoter activity and several upstream open reading frames (uORFs) were demonstrated at this region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 37 publications
0
40
0
Order By: Relevance
“…Interestingly, our in silico analysis revealed that the human ortholog of Tho1 is likely the Hcc-1 protein (see Fig. S2 in the supplemental material), which was identified as a highly expressed protein in human hepatocarcinoma and which has been shown in two-hybrid assays to bind the two DEAD box putative RNA helicases, hSUB2/UAP56/BAT1 and DDX39 (12,35).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, our in silico analysis revealed that the human ortholog of Tho1 is likely the Hcc-1 protein (see Fig. S2 in the supplemental material), which was identified as a highly expressed protein in human hepatocarcinoma and which has been shown in two-hybrid assays to bind the two DEAD box putative RNA helicases, hSUB2/UAP56/BAT1 and DDX39 (12,35).…”
Section: Resultsmentioning
confidence: 98%
“…The putative structural homolog of Tho1 in humans is a nuclear-matrix protein, Hcc-1 (see Fig. S2 in the supplemental material), which has been shown in two-hybrid assays to bind the two DEAD box putative RNA helicases, hSUB2/UAP56/BAT1 and DDX39 (12,35). Whether Tho1 might interact with RNAdependent ATPases important in the assembly of export-competent mRNPs is a possibility to be explored.…”
mentioning
confidence: 99%
“…Other members of the hnRNP family were reported to be related to HBV or HCC. For example, hnRNP K (64), hnRNP H/HЈ (65), and Hcc-1 (with sequence matches to hnRNP but localized to chromosome 7q22.1, which is different than hnRNP C1/C2) (66). But there has been no report about the up-regulation of hnRNP C1/C2 in HCC.…”
Section: Members Of Heat Shock Protein 70 and 90 Familiesmentioning
confidence: 99%
“…Hcc-1 cDNA level increased in pancreatic adenocarcinoma. The level also increased in a well-differentiated hepatocellular carcinoma but decreased as carcinoma progressed to a poorly differentiated stage [9].…”
Section: Introductionmentioning
confidence: 90%
“…CIP29 appears to be a new cytokineregulated protein involved in normal and cancer cell proliferation. The Hcc-1 and CIP29 genes were identified to encode the same protein [9,11].…”
Section: Introductionmentioning
confidence: 99%